Selective admission practices and problems in the public-supported trade-industrial schools. - Federizo, Antonio Tayao 1921- (s.n., 1966)
This is a description and analysis of the selective admission practices and problems in the trade-industrial schools in the country. The selective admission practices in the schools with respect to the orientation of prospective students, organization and functions of the staff, procedures, the criteria and the instruments were determined and evaluated based on the salient pointers in EPS Circular No. 4, s. 1959.